Analisa Gaya Geser Dasar dan Gaya Dalam Pada Kolom tehadap Penambahan Dinding Geser - Yayan Adi Saputro (Politeknik Negeri Lhokseumawe, 2020)
A flat plate is a two-way plate system with the plate load to be transferred directly to the column without having to pass through the beam structure. One of the advantages and strengths of this structure is that it can shorten or enhance the building. However, there are also some shortcomings in the use of flat plate structures, which are prone to lateral forces, mainly due to earthquake loads, because there is no beam structure causing the column and plate junction is not too strong, so that the structure is flexible and can cause danger of sliding the foundation. An alternative appeared to increase the strength of the structure is to add shear walls, where the influence of the shape and placement of the right layout is very important. The research method in the form of analysis in a 10-story building using a flat plate structure system with six shear wall modeling. With a distance between floors three meters, with four x-axis spans with a length of six meters and three y-axis spans with a length of five meters. The function of the building as a low-cost apartment is located in Jepara district with a medium type of land category. Analysis was performed with a SAP2000 software in three dimensions. The dynamic behavior reviewed includes the basic shear forces and internal forces in the column using the spectrum response analysis method. The shear force results are increased in Model VI for the X direction and Model III for the Y direction. The addition of lateral wall stiffener to the flat plate structure system affects the internal forces in the corner, edge and center columns.